Soil Aggregate Stability Index on Agricultural, Plantation, and Forest Lands - Hidayat, Yayat; Baskoro, Dwi Putro Tejo; Purwakusuma, Wahyu; Siregar, Mariana Sella; Ramadhi, Muhammad Haris Achyar (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
The soil aggregate stability index is one of the critical indicators of soil physical quality, primarily related to the soil's ability to absorb water into the soil and the soil's resistance to rainwater splashing and surface flow erosion in the soil erosion process. The study aimed to determine the soil aggregate stability index class criteria using the dry and wet sieving methods on the OSK 10701 sieve type and to identify the stability of soil aggregates on agricultural land, plantations, and forests around the IPB Dramaga campus. The transformation of the soil aggregate stability class criteria from the conventional sieve to the OSK 10701 sieve types gave excellent results with a coefficient of determination (R2) of 0.89. The soil aggregate stability index differs significantly between soil types and land uses. Podsolic Jasinga has a higher aggregate stability index than Podsolik Dramaga, Regosol Dramaga, and Latosol Dramaga in the upper layer (0-20 cm) and the lower layer (20-40 cm). Forests have a better aggregate stability index than conservation agricultural land, conventional agricultural land, rubber plantations, and oil palm plantations. The difference in stability index between land uses is closely related to soil organic matter contents. Although the soil is denser/more compact, the soil in oil palm and rubber plantations has a lower stability index and is classified as unstable.